#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# IF (A+B+C)=2S THAN SIN(S-A)+SIN(S-B)+SIN(S-C)-SINS WILL BE EQUAL TO

Vikas TU
14149 Points
4 years ago
( SIN(S-A)+SIN(S-B)) + (SIN(S-C)-SINS)
Now use sinc + sind and sinc – sind formulaes here simply,
=> 2cos(C-2S)/2sin(C/2)+2sin(C/2)cos(B-A)/2
=> 2sinC/2[cos(A+B)/2 +cos(B-A)/2] {cos-thetha = costhetha}
=> 2sinC/2 .[2cos(B/2)cos(A/2)]
=> 4cos(A/2)cos(B/2)sin(C/2)
Hence this would be the final soln.
Piyush Ranjan Singh
15 Points
one year ago
Sin(S-A)+Sin(S-B)+Sin(S-C)-SinS
Now use sinc + sind and sinc – sin d formulaes here and then simplify.
2Sin(2s-(A+B))/2 × Cos-(A-B)/2 + 2Cos(2s-c)/2 × Sin-c/2
=> 2Sinc/2 [cos(A-B)/2 - cos(A+B)/2]
=> 2Sinc/2 [-2sin2a/4 × Sin-2b/4]
=> 4Sin a/2 Sin b/2 Sin c/2.
given--> A+B+C =2S